Circadian Phase Control Using Adaptive Synchronization. Issue 14 (2015) - Vo-Tan, Phuoc; Ton-That, Long
Abstract: This paper deals with the phase control in Neurospora circadian rhythms. We show that this problem can be formulated as a chaos synchronization framework which was widely investigated in literature. A master-slave configuration is set up. The master dynamic with all known parameters generates the reference signals. The slave dynamic whose transcription rate of frq gene is considered as unknown is synchronized with the master signals by an adaptive control law. The simulation result shows a fast synchronization speed.